2007
DOI: 10.1007/s12232-007-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Yield management and perceptions of fairness in the hotel business

Abstract: yield management, revenue management, perceived fairness, hotels,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 28 publications
0
35
0
13
Order By: Relevance
“…Especially, framing and fencing condition have strong effects on fairness perception when customers are less familiar with a RM pricing. Mauri (2007) Yield management and perceptions of fairness in the hotel business Hotel Various aspects of customers' perceptions regarding RM are discussed and managerial techniques that hotel companies can employ to manage customer conflicts resulting from perceived unfairness due to RM practices are suggested.…”
Section: Wirtz and Kimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, framing and fencing condition have strong effects on fairness perception when customers are less familiar with a RM pricing. Mauri (2007) Yield management and perceptions of fairness in the hotel business Hotel Various aspects of customers' perceptions regarding RM are discussed and managerial techniques that hotel companies can employ to manage customer conflicts resulting from perceived unfairness due to RM practices are suggested.…”
Section: Wirtz and Kimesmentioning
confidence: 99%
“…Several researchers suggested that individuals' characteristics should be considered as potential covariates for future research of pricing issues (Xia et al, 2004). Mauri (2007) mentioned the social norms' possible variance among different market segments based on nationality, geography, social class, age, etc. However, to date, such issues have little, substantive exploration in the hospitality literature.…”
Section: Price Consciousnessmentioning
confidence: 99%
“…Hotels reduce this loss by adopting overbooking strategy to ensure full room occupancy and to maintain a high occupancy rate [9][10][11]. Overbooking is defined as selling more rooms than hotel capacity, which is performed when a certain number of booked customers are anticipated to cancel or not to show up [12].…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, customers have different perceptions of the fairness of a variable pricing strategy (Kimes and Wirtz, 2003a, b). Therefore, it is important to empirically examine the influence of this strategy on customer perceptions of price fairness (for eaxmple, Kahneman et al, 1986;Campbell, 1999;Kimes, 2002;Kimes and Wirtz, 2003a, b;Xia et al, 2004;Choi and Mattila, 2005;Martín-Consuegra et al, 2007;Mauri, 2007). On the basis of the applicability of a variable pricing strategy to beverage establishments, the following three research questions have emerged:…”
Section: Introductionmentioning
confidence: 99%